1996
DOI: 10.1007/bf00170846
|View full text |Cite
|
Sign up to set email alerts
|

Effect of urodilatin on platelet-activating factor-induced bronchoconstriction, vasoconstriction and edema formation in isolated rat lung

Abstract: In the isolated perfused rat lung, perfusion with platelet-activating factor causes bronchoconstriction, vasoconstriction and edema formation. The bronchoconstriction and vasoconstriction are largely mediated by thromboxane, whereas the edema formation is due to enhanced vascular permeability unrelated to eicosanoids. Since natriuretic peptides are known to relax smooth muscle and were suggested to attenuate enhanced vascular permeability, we investigated the effect of urodilatin on the PAF-induced alterations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2001
2001
2007
2007

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 21 publications
1
1
0
Order By: Relevance
“…The increased levels of ANP seen in sepsis might therefore exert protective effects on pulmonary permeability. Other studies in isolated perfused lungs showed that ANP has no effect on thromboxane-associated increases in pulmonary vascular permeability or may actually increase permeability in noninjured lungs (21,22). The latter findings are in keeping with the data presented here, as the ratio of lymph and plasma protein concentration reached 0.21 Ϯ 0.04 during ANP blockade at 44 hrs.…”
Section: In the Systemic Circulation Infusionsupporting
confidence: 93%
“…The increased levels of ANP seen in sepsis might therefore exert protective effects on pulmonary permeability. Other studies in isolated perfused lungs showed that ANP has no effect on thromboxane-associated increases in pulmonary vascular permeability or may actually increase permeability in noninjured lungs (21,22). The latter findings are in keeping with the data presented here, as the ratio of lymph and plasma protein concentration reached 0.21 Ϯ 0.04 during ANP blockade at 44 hrs.…”
Section: In the Systemic Circulation Infusionsupporting
confidence: 93%
“…PAF induces broncho-and vasoconstriction primarily by the release of thromboxane, which acts via the TP-R (7,51). Thus pharmacological analysis of PAF-induced broncho-and vasoconstriction has to take into account the fact that the agents tested may interfere not only with the pressor responses, but also with the production of thromboxane.…”
Section: Discussionmentioning
confidence: 99%